1923
DOI: 10.1002/ange.19230362102
|View full text |Cite
|
Sign up to set email alerts
|

Über das Lignin

Abstract: Der als ,Lignin" bezeichnete Anteil der pflanzlichen Zellmembran ist im Laufe der letzten Jahre in erhbhtem M d e wieder Gegenstand wissenschaftlicher Untersuchungen gewesen , deren jeweilige Ergebnisse mehrfach auch schon Veranlassung gegeben haben, die fUr seinen strukturellen Aufbau gegebenen Mbglichkeiten in ernsthafter Weise zu diskutieren l). Obwohl jedoch die frUheren Betrachtungen im wesentlichen noch aus rein spekulativer Anschauung erwachsen mubten, so ist doch heute mit ihnen und den unter BerUcksic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1923
1923
1936
1936

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Nuclear structure found by Schrauth (41) conditions may be expected to exist in a peat bog, the significance of the lignin-cellulose controversy may be regarded as considerably lessened by the work of Schrauth ( 41) who showed that one of the main products obtained by Willstátter and Kalb (49) in the reduction of lignin, cellulose, and other carbohydrates possessed properties practically identical with synthetic 9,10-perhydrobenzophenanthrene, Figure 1A. As a result of this study Schrauth (40) suggested that the coalforming vegetable matter may first have been converted into compounds of the nature shown in Figure IS. A molecule of this type would be expected readily to undergo condensation in various ways, giving molecules of unlimited size, and containing nitrogen and sulfur by reaction with other compounds.…”
Section: Chemistry Of Coal Formationsupporting
confidence: 52%
“…Nuclear structure found by Schrauth (41) conditions may be expected to exist in a peat bog, the significance of the lignin-cellulose controversy may be regarded as considerably lessened by the work of Schrauth ( 41) who showed that one of the main products obtained by Willstátter and Kalb (49) in the reduction of lignin, cellulose, and other carbohydrates possessed properties practically identical with synthetic 9,10-perhydrobenzophenanthrene, Figure 1A. As a result of this study Schrauth (40) suggested that the coalforming vegetable matter may first have been converted into compounds of the nature shown in Figure IS. A molecule of this type would be expected readily to undergo condensation in various ways, giving molecules of unlimited size, and containing nitrogen and sulfur by reaction with other compounds.…”
Section: Chemistry Of Coal Formationsupporting
confidence: 52%
“…Since Hawley and Harris (6) have shown that the aromatic compound, lignin, may be prepared from the aliphatic compound, cellulose, we need not concern ourselves with which of the two is the mother substance of coal. Furthermore, Schrauth (17) has shown that the products obtained by Willstátter and Kalb {21) from the reduction of lignin, cellulose, and sugars Figure 1 A. Hydrocarbon skeleton found by Schrauth (17) in the products obtained by Willstátter and Kalb (21) by the reduction of lignin, cellulose, and sugars. B.…”
mentioning
confidence: 99%
“…Further, while an average molecular weight of 300 appears low, an aromatic hydrocarbon of seven closely condensed rings has a molecular weight of only 302, and it should be noted that the molecular weight of the largest condensed aromatic structures which have been actually isolated from coal or pitch is smaller than this. It is also of interest that Fuchs (12), in picturing a hypothetical humic acid molecule, suggests a structure containing five condensed rings as the building unit, while Schrauth's (18) building element contains four six-membered and three five-membered condensed rings.…”
Section: Molecular Weight Measurementsmentioning
confidence: 99%